Multilingual and multimodal information access evaluation Second International Conference of the Cross-Language Evaluation Forum, CLEF 2011, Amsterdam, The Netherlands, September 19-22, 2011. Proceedings - Forner, Pamela (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the Second International Conference on Multilingual and Multimodal Information Access Evaluation, in continuation of the popular CLEF campaigns and workshops that have run for the last decade, CLEF 2011, held in Amsterdem, The Netherlands, in September 2011. The 14 revised full papers presented together with 2 keynote talks were carefully reviewed and selected from numerous submissions. The papers accepted for the conference included research on evaluation methods and settings, natural language processing within different domains and languages, multimedia and reflections on CLEF. Two keynote speakers highlighted important developments in the field of evaluation: the role of users in evaluation and a framework for the use of crowdsourcing experiments in the setting of retrieval evaluation.